CHRONIC INFLAMMATORY RESPONSES TO MICROGEL-BASED IMPLANT COATINGS - Bridges, Amanda W. (2010)
Inflammatory responses to implanted biomedical devices elicit a foreign body fibrotic reaction that limits device integration and performance in various biomedical applications. We examined chronic inflammatory responses to microgel conformal coatings consisting of thin films of poly(N-isopropylacrylamide) hydrogel microparticles cross-linked with poly(ethylene glycol) diacrylate deposited on poly(ethylene terephthalate) (PET). Unmodified and microgel-coated PET disks were implanted subcutaneously in rats for 4 weeks and explants were analyzed by histology and immunohistochemistry. Microgel coatings reduced chronic inflammation and resulted in a more mature/organized fibrous capsule. Microgel-coated samples exhibited 22% thinner fibrous capsules that contained 40% fewer cells compared to unmodified PET disks. Furthermore, microgel-coated samples contained significantly higher levels of macrophages (40%) than unmodified PET controls. These results demonstrate that microgel coatings reduce chronic inflammation to implanted biomaterials.